Cassini Flybys Reveal Details About Titan Seas and Lakes. (24th December 2013) - Showstack, Randy
Abstract : The Cassini spacecraft's flybys of Saturn's moon Titan reveal new details about the sizes, depths, and locations of the seas and lakes, whose liquid is mostly methane, that dot the moon's northern hemisphere, according to findings presented by scientists at a 12 December news briefing at the AGU Fall Meeting in San Francisco, Calif.